تأثير نظام الشبكيات الجائزية الطابقية والمدادات على استجابة الأبنية العالية البيتونية - دريد سلوم; وسام ماوردي (Tishreen University, 2019)
Tall building construction has been rapidly increasing worldwide. It is creating impact on innovative development of structural system for tall building. Recently, structural systems like bracing, outrigger and belt truss providing great approach for improve the response of tall buildings. The system of belt truss and outriggers has been used in many high building around the world during the last few decades as one of the structural methods for controlling excess displacements generated by lateral forces. It is important to minimize structural and non-structural damages caused by small and medium lateral forces generated by both wind and earthquakes. The belt truss and outriggers connect the external columns of the building, while the outriggers connect the external columns with the central core, thus the external columns abligate the core from by the outriggers. This research presents a reference study and studies the effect of using belt truss and outriggers as lateral force resisting system for high-rise concrete buildings subjected to earthquake load by comparing storey displacements and storey drifts due to response spectrum analysis, according to the seismic requirements of Lattakia city by performing a three dimensional analysis (3D) using (ETABS2016) for a building of 40 storey subjected to earthquake force. Storey displacements and storey drifts has been compared in five cases: • (MWBT): Model without belt truss and outriggers. • (MBT0.25): Model with one belt truss and outriggers at the level (0.25H). • (MBT0.5): Model with one belt truss and outriggers at the level (0.5H). • (MBT0.75): Model with one belt truss and outriggers at the level (0.75H). • (MBTH): Model with one belt truss and outriggers at the level (H). Storey drifts reduction in the building with belt truss and outriggers were (42.31%, 42.42%, 40.03%, 33.96%) respectively as compared to a model without any belt truss and outrigger system (BWT), and the storey displacements reduction were (3.63%, 4.84%, 4.88%, 2.38%) respectively. إن إنشاء الأبنية العالية في تزايد مستمر حول العالم، مما أدى لخلق ضرورة التطور المتسارع في الأنظمة الإنشائية لتلك الأبنية. حالياً، تُعد الأنظمة الإنشائية كالتربيط، والمدادات، والشبكيات الجائزية الطابقية من الطرق المثلى المعتمدة في تحسين استجابة الأبنية العالية. استخدم نظام الشبكيات الجائزية الطابقية والمدادات في الكثير من الأبنية العالية حول العالم خلال العقود الأخيرة، كإحدى الطرق الإنشائية للتحكم بالإزاحات الزائدة المتولدة عن القوى الجانبية، وذلك لم له من أهمية في تقليل الأضرار الإنشائية والغير إنشائية التي تسببها القوى الجانبية الصغيرة والمتوسطة المتولدة عن كل من الرياح والزلازل. إذ يربط الجائز الشبكي الأعمدة الخارجية للمبنى، بينما تربط المدادات الأعمدة الخارجية مع النواة المركزية، وهكذا تقيد الأعمدة الخارجية النواة من الدوران من خلال المدادات. يقدم هذا البحث الدراسة المرجعية ودراسة تأثير استخدام الشبكيات الجائزية الطابقية والمدادات (belt truss and outriggers) كنظام إنشائي مقاوم للأحمال الجانبية من خلال مقارنة الانتقالات الطابقية والإزاحات الطابقية الناجمة عن التحليل باستخدام طيف الاستجابة التصميمي بما يتوافق مع المتطلبات الزلزالية لمدينة اللاذقية من خلال إجراء التحليل ثلاثي الأبعاد لنموذج إنشائي مفترض لبناء عال بيتوني مؤلف من (40) طابقاً معرض لقوى الزلازل، وذلك بمساعدة برنامج التحليل الإنشائي(ETABS2016)، وقد تمت مقارنة الانتقالات الطابقية والإزاحات الطابقية للمبنى في خمس حالات: • المبنى دون نظام الشبكيات الجائزية الطابقية والمدادات (BWT). • المبنى مع نظام الشبكيات الجائزية الطابقية والمدادات (BT0.25) عند الارتفاع (0.25H). • المبنى مع نظام الشبكيات الجائزية الطابقية والمدادات (BT0.5) عند الارتفاع (0.5H). • المبنى مع نظام الشبكيات الجائزية الطابقية والمدادات (BT0.75) عند الارتفاع (0.75H). • المبنى مع نظام الشبكيات الجائزية الطابقية والمدادات (BTH) عند الارتفاع (H). وقد تبين أن التخفيضات في الإزاحات الطابقية للمبنى مع نظام الشبكية الجائزية الطابقية والمدادات هي على التوالي42.31%, 42.42%, 40.03%, 33.96%) ) مقارنة مع الإزاحات الطابقية للمبنى دون وجود الشبكيات الجائزية الطابقية والمدادات (BWT). والتخفيضات في الانتقالات الطابقية هي على التوالي (3.63%, 4.84%, 4.88%, 2.38%) مقارنة مع الانتقالات الطابقية للمبنى دون وجود الشبكيات الجائزية الطابقية والمدادات.